Exploring the Livelihood Assets Utilisation and the Business Sustainability Among Garment Businesses at Tingkir Lor District, Salatiga - Raung, Sally Agustina (KRITIS, 2024)
ABSTRACT This paper explores how accummulation of livelihood assets of entrepreneur  affects the business sustainability of MSMEs positively. Bringing up a case study of entrepreneurs running Small Medium garment businesses in Tingkir Lor, Salatiga, this paper provides empirical evidence of how optimum utilization of livelihood assets at the early stage of their business has improved their capabilities to develop their business. Using qualitative research methods, this article analyzes the entrepreneurs’ strategies in exploiting livelihood assets from start up to business development. Optimum utilization of livelihood assets in those two business stages has improved the capabilities of the entrepreneurs to sustain their livelihoods. Keywords: Livelihood, MSMEs, Livelihood assets, Strategy, Tingkir Lor.